Aligning diamond particles inside BN honeycomb for significantly improving thermal conductivity of epoxy composite. (3rd May 2022) - Du, Xinxin; Yang, Wulin; Zhu, Jiajun; Fu, Licai; Li, Deyi; Zhou, Lingping
Abstract: Construction of interconnected heat conductive network in polymer is essential to effectively transport heat in thermal management materials. Due to synergistic effect, hybrid fillers are increasingly utilized in composites for higher thermal conductivity, but how to achieve better enhancement is still an open problem. In this paper, a pod-like 3D interconnected heat percolation network was obtained by aligning diamond inside boron nitride (BN) honeycomb. The BN honeycomb used as secondary templets was prepared by ice template method. Subsequently, the epoxy (EP) and diamonds were filled into it simultaneously by vacuum infiltration. SEM and computed tomography results demonstrated that highly ordered thermal conductive channels have been constructed. When the content of BN is 7 vol% and diamond is 12 vol%, the thermal conductivity of the composite is as high as 2.720 W/(m·K), which is 12.5 and 5.8 times higher than that of pure EP and randomly mixed sample, respectively. To better understand the enhance mechanism, through the parallel structural model calculations, the effective thermal conductivity of the local tightly packed diamond part was increased from 1.210 W/(m·K) to 11.318 W/(m·K) in the composite. The findings suggested that the bridging effect of BN wall on connecting diamond particles also contributed to enhanced property of the composite. This study offers a novel strategy for obtaining higher thermal conductivity with low filler loading in hybrid composites. Graphical abstract: Image 1 Highlights: h-BN honeycomb network was obtained by the ice template method. Diamond particles directionally aligned along the BN honeycomb during the infiltration. The pod-like continuous networks obviously enhanced thermal conductivity (K) of the composites. K of the composites is 5.8 times higher than that of randomly mixed sample. Enhancement mechanism of the pod-like network on heat transfer is revealed.